Web Based Online Auction System Design (LELANGI) - Winarsih Winarsih; Sutikman Sutikman (INFOKUM, 2022)
The development of online magazine information technology in Indonesia has made a lot of progress, this has also been followed by technological developments in reducing paper use. Auction via the internet (e-auction) is an auction modernization that allows buyers or bidders to participate by bidding in writing without the need to be present at an auction venue, but simply via the internet. Auctionis the process of buying and selling goods or services by offering to a bidder, bidding a higher price, and then selling the item to the highest bidder. Because students need more goods that are of good quality and of course cheap, usually almost all of the items that are auctioned are original. This auctionis an interactive web that presents an online auction that can only be used by students. This interactive web auction is like other online buying and selling such as tokopedia, blibli, etc. It's just that this sale and purchase prioritizes whoever bids the higher price, he wins. Items that may be auctioned are only one item. It is prohibited to auction other than goods, such as animals, plants and even buying and selling of people is not permitted.